Incidence des modes de partenariat à l'école élémentaire sur la polyvalence des maîtres et sur les représentations des élèves - Devos-Prieur, Odile; Loubet-Gauthier, Elisabeth (Recherche & formation, 2002)
The profession of primary school teachers has deeply changed in about twenty years. This study focuses on the evolution of the concept of versatility when a teacher has to work with a partner. What are the main changes in the concept of versatility occuring when teachers have to work in pairs ? Is there any influence on the representation of the subject they are supposed to teach together ? To what extent are school children aware of the benefits coming from this team work ? The main purpose of our study is to understand how and why the